Attention Deficit Hyperactivity Disorder (ADHD): Awareness, Attitudes, and Behavioural Responses among Aspiring Teachers in North East India - Padmavathy, R. D. (Voices of Teachers and Teacher Educators, 2024)
The global rate of attention deficit hyperactivity disorder (ADHD) among school-aged children, ranging from 3 to 17 years, is gradually increasing. Despite this growing prevalence, previous studies have highlighted a gap in research specifically related to ADHD and aspiring teachers. The present study aims to address this gap by examining the awareness, attitudes, and behavioural responses towards ADHD among aspiring teachers in North East India. The study seeks to assess their level of awareness, attitudes, and behavioural responses concerning ADHD. To gather data, the researcher employed a descriptive survey research design and a convenience sampling method, involving 88 aspiring teachers. Data collection utilised a self-constructed Knowledge and Awareness towards ADHD tool, in addition to the “attention deficit hyperactivity disorder (ADHD) Tool” developed by Jain and Gunthey (2013). The findings indicate that the aspiring teachers’ levels of awareness, attitude, and behaviour response towards ADHD are generally average. Specifically, 65% of the aspiring teachers demonstrated good knowledge, 77% exhibited a desirable attitude, and 75% showed good behaviour related to ADHD. Overall, 53% of the participants displayed an acceptable level of awareness, attitude, and behaviour towards ADHD. While aspiring teachers possess above-average knowledge about inattention, hyperactivity, and impulsivity, they struggle to clearly distinguish the specific characteristics of ADHD.